PENGARUH CHLORHEXIDINE 0,2% SEBAGAI ORAL HYGIENE TERHADAP PENCEGAHAN VENTILATOR ASSOCIATED PNEUMONIA (VAP) PADA PASIEN GAGAL NAFAS DI RUANG ICU RUMAH SAKIT IMMANUEL BANDUNG - rumtily, marlin Jomima rumtily (Institut Kesehatan Immanuel, 2025)
Background: Ventilator-Associated Pneumonia (VAP) is one of the most common nosocomial infections occurring in patients using mechanical ventilators for more than 48 hours, particularly in Intensive Care Units (ICUs). One of the main contributing factors to VAP is bacterial colonization in the oral cavity due to inadequate oral hygiene, especially in unconscious patients who are unable to perform self-care. Objective: This study aims to determine the effect of 0.2% chlorhexidine oral hygiene intervention in preventing the occurrence of VAP in patients with respiratory failure using ventilators in the ICU of RS Immanuel Bandung. Method: This study used a case study approach, applying oral hygiene using 0.2% chlorhexidine to ventilated patients. Data were collected through direct observation and clinical documentation, focusing on signs of infection before and after the intervention. Results: The results showed a reduction in infection indicators after oral hygiene, such as decreased body temperature, reduced secretion volume, and improvement in clinical observations. The use of 0.2% chlorhexidine was proven effective in reducing the number of microorganisms in the oral cavity and preventing aspiration of pathogens into the lower respiratory tract. Conclusion: Oral hygiene using 0.2% chlorhexidine is an effective nursing intervention in preventing Ventilator-Associated Pneumonia in patients with respiratory failure on mechanical ventilation. This intervention can be integrated into the standard nursing care protocol in ICUs to enhance patient care quality and safety. Keywords: Respiratory failure, Ventilator-Associated Pneumonia, Oral hygiene, 0.2% Chlorhexidine, ICU